Observation on dromedary (Camelus dromedarius) welfare and husbandry practices among nomadic pastoralists - Maurizio Dioli (Pastoralism, 2022)
Abstract Animal welfare is an important topic for consideration within every livestock husbandry sector. Welfare frameworks have recently been developed for intensively and semi-intensively husbanded dromedaries. These do not fit the reality of dromedaries under pastoral husbandry, and no specific analysis exists on dromedary welfare when reared under pastoral nomadic conditions. This article examines the existing husbandry practices utilised by nomadic pastoralists with the aim of improving the understanding of dromedary welfare in a nomadic pastoral husbandry system.